Pyrolysis kinetics and thermal characteristics of microalgae Nannochloropsis oculata and Tetraselmis sp. - KAZAN, DİLEK (ELSEVIER SCI LTD, 2015)
In this study non-isothermal thermogravimetric analysis were used to investigate pyrolysis behavior and kinetics of microalgae Nannochloropsis oculata (NO) and Tetraselmis sp. (TS). TG/DTG experiments at different heating rates were carried out. Heating rates had slight effect on the decomposition trend, however the maximum temperature and peak of weight loss rate in the DTG curves shifted towards higher temperature with the increase in heating rate. The average activation energy and pre-exponential factor for pyrolysis of NO and TS were estimated by distributed activation energy model. The highest activation energies were observed as 152.20 and 334 kJ/mol for NO and TS, respectively, at various conversions. The pre-exponential factors for the corresponding activation energies were observed to be in the order of 10(8)-10(13) and 10(12)-10(25) s(-1) for NO and TS, respectively. Calculated kinetic parameters were used to predict devolatilization curves and results were in well agreement with experimental data. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Microalgae; TGA; Pyrolysis; Kinetics; Distributed activation energy model; ACTIVATION-ENERGY MODEL; THERMOGRAVIMETRIC ANALYSIS; BIOMASS; COMBUSTION; DECOMPOSITION; WASTE; COCOMBUSTION; BEHAVIOR; GRAINS; BLEND